German Imperialism in China: The Leasehold of Kiaochow Bay (1897–1914). (3rd July 2019) - Coco, Orazio
Abstract : In 1897, German imperial navy invaded Kiaochow Bay (in Chinese Pīnyīn known as Jiāozhōu). After signing a convention with Chinese imperial government, the territory was leased to imperial Germany for 99 years. German governors provided the territory with modern and efficient infrastructures and the protectorate became the highest expression of German national pride in Asia. However, the authorities also implemented a controversial social system, mainly based on segregation of the local population and pursued an economic project aiming to the exploitation of the natural resources of the territory. In November 1914, Kiaochow was occupied by Japanese forces and article 156 of the Treaty of Versailles confirmed the acquisition of the territory in favor of Japan. This essay examines the events related to the German occupation using primary sources written by diplomats and citizens who lived in the protectorate and highlights the consequences of that important experience for modern China.